Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1099/00207713-29-4-312
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Electrophoretic Forms of Transaldolase and 6-Phosphogluconic Dehydrogenase and Their Relationships to the Taxonomy and Ecology of the Bifidobacteria

Abstract: The electrophoretic patterns of the transaldolases and 6-phosphogluconate dehydrogenases (GPGD) of 1,206 strains, each belonging to one of 24 named species of the genus Bifidobacterium, were determined by means of starch-gel electrophoresis. All of these strains were previously assigned to species on the basis of their deoxyribonucleic acid homology relationships and were selected so as to include all known phenotypes and habitats. Fourteen electrophoretic forms of transaldolase and 19 of nicotinamide adenine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…When the guideline value of 13% is used in conjunction with tree topology information (including confidence values), it seems likely that B. Zongum ATCC 15708 and B. infantis ATCC 15697T should be considered subspecies of a single species. Our doubt concerning the advisability of recognizing B. infantis and B. Zongum as separate species is also supported by DNA-DNA hybridization data which showed that the levels of DNA similarity between the two species range from 65 to 80% (48).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the guideline value of 13% is used in conjunction with tree topology information (including confidence values), it seems likely that B. Zongum ATCC 15708 and B. infantis ATCC 15697T should be considered subspecies of a single species. Our doubt concerning the advisability of recognizing B. infantis and B. Zongum as separate species is also supported by DNA-DNA hybridization data which showed that the levels of DNA similarity between the two species range from 65 to 80% (48).…”
Section: Discussionmentioning
confidence: 96%
“…Numerical taxonomy analysis, which requires data for many characteristics, has been used to circumscribe clusters and to describe strains. Morphological traits, carbohydrate metabolism data, DNA G + C contents (3), electrophoretic patterns (22,48,50), serologic data (44, 58, 59), cell wall compositions (22), and rRNA gene restriction patterns (26) have been used to subdivide Bifidobacterium species (for a review, see reference 3). Major advances in our understanding of the taxonomy of members of the genus Bijidobacterium have come from the DNA-DNA hybridization studies performed by Scardovi et al (49,54,55,57).…”
mentioning
confidence: 99%
“…According to the definition of a species, as cited by Wayne et al (27), and the standard errors calculated by Grimont et al (13) (about 4% in the S1 nuclease method and about 1.7"C in ATm determinations), only one strain (DSM 20218) could be considered a B. infantis strain. Two new isolates (CUETM 89-193 and CUETM 89-240) could represent part of the continuum described by Scardovi et al (20). All of the other strains are B. longum strains.…”
Section: (20)mentioning
confidence: 62%
“…infantis group. The levels of DNA relatedness between the two species were found to vary from 65 to 80% (20,23,25). Later, in 1983, Lauer and Kandler (14) performed DNA-DNA hybridization experiments with the type strains and obtained values of 62 to 63%.…”
Section: Resultsmentioning
confidence: 99%
“…However, fermentative characteristic alone could not lead to positive species identification of the strain. Scardovi et al (13) proved that strain of B. catenulatum exhibited fermentation pattern similar to those of B. adolescentis. B. infantis and B. longum are also difficult to distinguish using phenotypic characterisation (1).…”
Section: Discussionmentioning
confidence: 98%